Budaya, Agama, dan Makna Volunterisme bagi Kader Warga Peduli AIDS di Kota Bandung - Erna Herawati (Universitas Andalas, 2019)
HIV epidemic in Indonesia has been last for three decades and the members of the community have participated in the prevention and intervention. Warga Peduli AIDS (WPA) is an action by a group of local residents in Bandung City who concerned about HIV and AIDS. This action has been one of examples of community participation in responding to the epidemic. The action includes participation in meetings held by NGOs and city government to discuss prevention at the community level, dissemination of information about epidemic preventions; and providing social support for people living with HIV and AIDS. This study aims at describing motives that drive the WPA activist (better known as WPA Kader) to carry out an action, and how they view the meaning of their action. This study was conducted in a qualitative approach using an ethnographic model. This study finds that WPA Kader derived their motive of action from religious and cultural values, and their action is a combination of altruism and self-interest to pursue their personal spiritual satisfaction. In line with this motive, they view their action as part of their religious and cultural expression; instead of merely a community-based action to respond to a timely health issue.